2021
DOI: 10.1063/5.0044106
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and vacancy defects in silicon. A quantum mechanical characterization through the IR and Raman spectra

Abstract: The Infrared (IR) and Raman spectra of various defects in silicon, containing both oxygen atoms (in the interstitial position, Oi) and a vacancy, are computed at the quantum mechanical level by using a periodic supercell approach based on a hybrid functional (B3LYP), an all-electron Gaussian-type basis set, and the Crystal code. The first of these defects is VO: the oxygen atom, twofold coordinated, saturates the unpaired electrons of two of the four carbon atoms on first neighbors of the vacancy. The two rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For example, the stable states of the vacancy and its complexes with impurities, their formation energies were theoretically investigated in previous researches [1][2][3][4][5]. The experimental studies [6][7][8][9][10] indicated the possibility of forming the complexes of a vacancy with an impurity oxygen and hydrogen atoms in stable states, and the kinetic energies of the formation are given. This type of defects are very mobile and could be identified directly only in the silicon of 𝑝-type.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the stable states of the vacancy and its complexes with impurities, their formation energies were theoretically investigated in previous researches [1][2][3][4][5]. The experimental studies [6][7][8][9][10] indicated the possibility of forming the complexes of a vacancy with an impurity oxygen and hydrogen atoms in stable states, and the kinetic energies of the formation are given. This type of defects are very mobile and could be identified directly only in the silicon of 𝑝-type.…”
Section: Introductionmentioning
confidence: 99%